Interiorizar “Jesus Cristo”: Programa narrativo-biográfico de D. Luciano Mendes de Almeida (Internalizing “Jesus Christ”: The biographical narrative program on D. Luciano Mendes de Almeida) - DOI: 10.5752/P.2175-5841.2012v10n27p959 - Buarque, Virgínia Albuquerque de Castro (Horizonte, 2012)
This article aims at reconstructing the meaning given by D. Luciano Mendes de Almeida (1930-2006), to his own biographical trajectory. D. Luciano was auxiliary bishop of Saint-Paul and Archbishop of Mariana, secretary and president of the CNBB, and also vice president of CELAM. The configuration he made of himself appears to be paradoxical: instead of strengthening a personal identity, it assumes a dynamic anthropological and religious self-emptiness and a mediating performance in favor of ternary relations between God and the subject itself, a process called by the Archbishop as the "internalization of the figure Jesus Christ." With a theoretical support coming from semiotics and religious history, this process of internalization is understood in this article as a specific narrative program which has acquired unique forms over the centuries, with emphasis on Ignatians spirituality, while preserving its conception as an act of faith on behalf of the competency given to an Other. The article also suggests that ,nowadays, that internalization of the figure of Jesus Christ approaches the reported testimony, given the ethical engagement raised by it, which reconfigures the subject in the sharing of experiences of life that are brought into discourse.